Synaptotagmin 11 interacts with components of the RNA‐induced silencing complex RISC in clonal pancreatic β‐cells. Issue 14 (29th May 2014) - Milochau, Alexandra; Lagrée, Valérie; Benassy, Marie-Noëlle; Chaignepain, Stéphane; Papin, Julien; Garcia-Arcos, Itsaso; Lajoix, Anne; Monterrat, Carole; Coudert, Laetitia; Schmitter, Jean-Marie; Ochoa, Begoña; Lang, Jochen
Abstract : Synaptotagmins are two C2 domain‐containing transmembrane proteins. The function of calcium‐sensitive members in the regulation of post‐Golgi traffic has been well established whereas little is known about the calcium‐insensitive isoforms constituting half of the protein family. Novel binding partners of synaptotagmin 11 were identified in β‐cells. A number of them had been assigned previously to ER/Golgi derived‐vesicles or linked to RNA synthesis, translation and processing. Whereas the C2A domain interacted with the Q‐SNARE Vti1a, the C2B domain of syt11 interacted with the SND1, Ago2 and FMRP, components of the RNA‐induced silencing complex (RISC). Binding to SND was direct via its N‐terminal tandem repeats. Our data indicate that syt11 may provide a link between gene regulation by microRNAs and membrane traffic. Abstract : Role and distribution of Ca 2+ ‐insensitive membrane proteins of the synaptotagmin family, such as syt11, are unknown. Mass spectrometry and pull‐down identified binding partners, including SNARE proteins as well as Ago2, FMRP and SND1. These novel interactions of a synaptotagmin may link gene regulation by microRNAs and membrane traffic.